Anti-erosion effect of an experimental varnish on eroded dentin - Filho, George Monteiro; Barros, Antonia Patricia Oliveira [UNESP]; Fernandes, Gabriela Carvalho Santos; De Albuquerque Jasse, Fernanda Ferreira; Kuga, Milton Carlos [UNESP]; Alencar, Cristiane De Melo (FapUNIFESP (SciELO), 2023)
This in vitro study evaluated the effect of an experimental varnish containing 20% nano-hydroxyapatite (nHAP) associated with 5% stannous chloride (SnCl2) against erosive-abrasive wear on bovine dentin. Samples of bovine cervical dentin were pre-eroded (0.3% citric acid, pH 2.6 for 10 minutes) and randomized into 4 groups (n=10): Control group - experimental varnish without active ingredient (CG); experimental varnish containing 20% nHAP (nHG); experimental varnish containing 5% SnCl2 (24.800 ppm Sn2+) (SnG); experimental varnish containing 20% nHAP associated with 5% SnCl2 (18.300 ppm Sn2+) (nHSnG). After applying the materials, the erosive-abrasive challenges were performed for five days. Erosive dentin loss and analysis of the pattern of dentinal obliteration were performed by 3D confocal laser microscopy. A one-way ANOVA/Bonferroni test was performed to analyze the data (a=0.05). The SnG and nHSnG experimental groups presented more effectiveness in preventing erosive wear when compared to the other groups (p<0.05). There was no statistically significant difference between the SnG and nHSnG groups (p = 0.731) in tooth structure dentin loss. Regarding the amount of open dentinal tubules, the highest amount of obstructed dentinal tubules was demonstrated in SnG and nHSnG (p < 0.05) when compared to the others. Between SnG and nHSnG there was no significant difference (p = 0.952) in the amount of closed dentinal tubules in the dentin. Experimental varnishes containing 5% SnCl2 associated or not with 20% nHAP showed to be a promising strategy in preventing erosive-abrasive wear of dentin. In addition, nHSnG was able to obliterate dentinal tubules.
Keywords: Dentin; Erosion; Nano-hydroxyapatite; Profilometry